2020
DOI: 10.1136/bmjopen-2020-040898
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on surgical neuro-oncology multi-disciplinary team decision making: a national survey (COVID-CNSMDT Study)

Abstract: ObjectivesPressures on healthcare systems due to COVID-19 has impacted patients without COVID-19 with surgery disproportionally affected. This study aims to understand the impact on the initial management of patients with brain tumours by measuring changes to normal multidisciplinary team (MDT) decision making.DesignA prospective survey performed in UK neurosurgical units performed from 23 March 2020 until 24 April 2020.SettingRegional neurosurgical units outside London (as the pandemic was more advanced at ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…Clinical trial enrollment was also affected as 18.6% of patients lost the ability to participate due to COVID-19 [ 157 ]. In the United Kingdom, 10.7% of patients had to change their management plans with 86% no longer undergoing surgery [ 158 ]. These delays are two-sided as hospital resources were needed to treat COVID-19 patients, and these individuals are considered high-risk.…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…Clinical trial enrollment was also affected as 18.6% of patients lost the ability to participate due to COVID-19 [ 157 ]. In the United Kingdom, 10.7% of patients had to change their management plans with 86% no longer undergoing surgery [ 158 ]. These delays are two-sided as hospital resources were needed to treat COVID-19 patients, and these individuals are considered high-risk.…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…Multiple studies have investigated the impact of COVID‐19 pandemic on both oncological and nononcological activities with variable findings 2–7 . We thus wanted to define the real ability in preserving the oncological surgical practice at our Institution during the most critical months of the epidemic by analyzing the surgical pathology activity of our units.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple neuro-oncology guidelines from high-volume centers in HICs have recommended the following: symptom-based and disease-based patient triaging; patient segregation based on COVID-19 status; PPE based on World Health Organization recommendations with emphasis on PAPR for level III; limiting aerosolizing procedures in the OR; use of negative-pressure ORs for COVID-19–positive patients; use of negative-pressure ICUs for postoperative patients (in case these patients develop COVID-19 infection); immediate postoperative step-down areas; the use of telemedicine for outpatient consults; the use of hypofractionated RT; and the use of less toxic chemotherapy protocols in managing neuro-oncology patients. 1 , 2 , 6 , 7 , 8 , 9 , 10 , 11 , 31 , 32 , 33 , 34 Our review has shown that the experience and practice patterns reported in LMICs were generally similar to these recommendations but had some differences attributed to resource availability and patient preferences.…”
Section: Discussionmentioning
confidence: 79%